2010
DOI: 10.1007/s11160-010-9158-6
|View full text |Cite
|
Sign up to set email alerts
|

Spawning period of Mediterranean marine fishes

Abstract: We collected all available information (i.e. international and local journals, conference proceedings, theses, technical reports) on the spawning season (n = 511 stocks, 168 species), gonadosomatic index (n = 237 stocks, 81 species) and sex ratio (n = 97 stocks, 68 species) of Mediterranean marine fish. The 511 stocks represented 20 orders (most were Perciformes, 283 stocks) and 65 families (most were Sparidae: 17 species and 63 stocks). Overall, 346 stocks (128 species) spawned between April and August, 139 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
96
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(114 citation statements)
references
References 147 publications
15
96
1
2
Order By: Relevance
“…On the contrary, during winter months, meroplanktonic taxa constituted a significant part of the zooplankton community and in some cases the majority of total zooplankton abundance. The presence of the larvae and especially the eggs of the anchovy (Engraulis encrasicolus) in summer months coincide with its main reproductive period in the Mediterranean (Tsikliras et al, 2010). Larvae and eggs of this species have also been reported from other coastal lakes (e.g.…”
Section: Zooplanktonmentioning
confidence: 82%
“…On the contrary, during winter months, meroplanktonic taxa constituted a significant part of the zooplankton community and in some cases the majority of total zooplankton abundance. The presence of the larvae and especially the eggs of the anchovy (Engraulis encrasicolus) in summer months coincide with its main reproductive period in the Mediterranean (Tsikliras et al, 2010). Larvae and eggs of this species have also been reported from other coastal lakes (e.g.…”
Section: Zooplanktonmentioning
confidence: 82%
“…Moreover, our samplings have been carried out with an annual periodicity. In the Mediterranean Sea, the common pandora generally spawns in spring/summer (Tsikliras et al 2010), a second spawning period in autumn has been reported by some authors (Dieuzeide et al 1955;Ghorbel and Ktari 1982;Vassilopoulou and Papaconstantinou 1990). Discordant opinions regard the time of sex reversal: it has been reported to occur during the prespawning, spawning or postspawning season in different studies (D'Ancona 1949;Larrañeta 1953;Zei and Zupanovio 1961).…”
Section: Discussionmentioning
confidence: 74%
“…However, the sexual pattern seems to be much more complex as both primary males and specimens, which are still females at the known maximum size, are frequently identified (Larrañeta 1964). The spawning season lasts from March to November in the Mediterranean Sea and from May to August in the Atlantic waters (Hashem and Gassim 1981;Girardin and Quignard 1985;Papaconstantinou et al 1988;Livadas 1989;Pajuelo and Lorenzo 1998;Hoşsucu and Ç akır 2003;Coelho et al 2010;Tsikliras et al 2010). Sexual maturity is reached between the second and the third year of life (Girardin and Quignard 1985;Pajuelo and Lorenzo 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Exceptional behavioural patterns or tactics (e.g., bourgeois and parasitic sperm competing males: Taborsky 1998, Gonçalves et al 2005 and diversions from the norm (e.g., unexpected reproductive strategy: Freon et al 1997) may need more research and discussion and justify also a research article. Ichthyoplankton surveys also provide important information on the spawning of fishes, such as defining the extent of the spawning period (e.g., Tsikliras et al 2010), but are not considered here as they belong to a scientific field of their own.…”
Section: Definitions and General Suggestionsmentioning
confidence: 99%
“…The number of articles published in the primary literature that deal with the reproductive biology of fishes has increased progressively with time (for the Mediterranean Sea; see Tsikliras et al 2010, Tsikliras and Stergiou unpublished ** ). Globally, since 2002, such articles have averaged >1100 items per year (Fig.…”
mentioning
confidence: 99%